2017
DOI: 10.1001/jamafacial.2017.0296
|View full text |Cite
|
Sign up to set email alerts
|

Complete Philtrum Reconstruction on the Partial-Thickness Cross-Lip Flap by Nasolabial Muscle Tension Line Group Reconstruction in the Same Stage of Flap Transfer

Abstract: IMPORTANCEThe blood supply pattern of the partial-thickness musculomucosal pedicle flaps is different from the traditional Abbe flap. The arterial blood supply and venous drainage are highly reliable during clinical practice.OBJECTIVE To describe the reconstruction of the philtrum in the cross-lip flap transfer using nasolabial muscle tension line group reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…This method enables detailed visualization of the muscle fibers. We utilized this method to study the nasolabial muscles and those at the corner of the mouth, obtaining satisfactory results (Yin et al, 2015, 2017; Ma et al, 2016; Wu and Yin, 2016; Jiang et al, 2018; Sun et al, 2018). In this study, after micro-CT scanning, all images showed good contrast between the connective tissues and muscle fibers, allowing detailed morphologic observations of the muscle fibers in the 2-D projection images, including their insertion and connections.…”
Section: Discussionmentioning
confidence: 99%
“…This method enables detailed visualization of the muscle fibers. We utilized this method to study the nasolabial muscles and those at the corner of the mouth, obtaining satisfactory results (Yin et al, 2015, 2017; Ma et al, 2016; Wu and Yin, 2016; Jiang et al, 2018; Sun et al, 2018). In this study, after micro-CT scanning, all images showed good contrast between the connective tissues and muscle fibers, allowing detailed morphologic observations of the muscle fibers in the 2-D projection images, including their insertion and connections.…”
Section: Discussionmentioning
confidence: 99%
“…A similar flap like the Estlander flap is a single-stage reconstruction, whose point of rotation is at the commissure 13,18 . Abbe flap and Estlander flap are cross-lip flaps; both can be used for reconstruction of full-thickness defects affecting 30% to 60% of the width of either lip medial to the commissure 19,20 . As for a large fullthickness defect greater than two-thirds of the lip, transfer of tissue from distant sites or adjacent cheek tissue is needed to avoid microstomia 13 .…”
Section: Discussionmentioning
confidence: 99%
“…13,18 Abbe flap and Estlander flap are cross-lip flaps; both can be used for reconstruction of full-thickness defects affecting 30% to 60% of the width of either lip medial to the commissure. 19,20 As for a large fullthickness defect greater than two-thirds of the lip, transfer of tissue from distant sites or adjacent cheek tissue is needed to avoid microstomia. 13 Nasolabial fold flap, bilateral cheek advancement flaps, Webster technique, flaps from the scalp and forehead, and submandibular, deltopectoral, pectoralis-major, sternocleidomastoid have been described in reconstruction of large full-thickness lip defects.…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical treatment involves induction of apical development with appropriate drugs after infection control. However, drug-induced apical development often and sometimes fails to increase the thickness of root canal wall and tooth resistance, resulting in poor therapeutic effect [12]. Therefore, there is need to develop a biological therapy that can promote the growth of tooth root and regeneration of dentin.…”
Section: Effects Of Erk and P38mapk Signaling Pathways On Mrna And Pr...mentioning
confidence: 99%